Neurofilament light chain (Nf-L) in cerebrospinal fluid and serum as a potential biomarker in the differential diagnosis of neurological diseases in cattle - Giorgia Di Muro; Carlotta Tessarolo; Giulia Cagnotti; Alessandra Favole; Sara Ferrini; Ugo Ala; Claudio Bellino; Giuliano Borriello; Marina Gallo; Giulia Iamone; Barbara Iulini; Marzia Pezzolato; et al. (Veterinary Research)
Abstract Neurofilament light chain (Nf-L) is a biomarker for axonal damage in human neurology but is understudied in cattle. With this study we wanted to determine Nf-L stability at two different storage temperatures and Nf-L levels in healthy cattle and the relationship with age, evaluate whether Nf-L holds diagnostic potential for neurological disorders, and whether an association exists between Nf-L in serum and in cerebrospinal fluid (CSF). To do this, we measured Nf-L levels in CSF and serum samples from 49 healthy and 75 sick cattle. Storage at −80 °C or −20 °C had no impact on Nf-L concentration. Physiological median Nf-L levels were 6.3 pg/mL (serum) and 414 pg/mL (CSF) in calves and 5.5 pg/mL (serum) and 828 pg/mL (CSF) in adult cattle. There was no association between Nf-L levels in CSF and calf age (r2 0.07, p = 0.13), while a weak association was found for Nf-L in serum (r2 0.26, p = 0.01), and a significant association in adult cattle (CSF, r2 0.69, p = 0.0001; serum, r2 0.68, p = 0.0003). CSF Nf-L levels were higher in samples from animals with degenerative (median Nf-L 49971 pg/mL) and infectious central nervous system (CNS) disorders (median Nf-L, age < 2 months 8863 pg/mL; age 2–12 months 17474 pg/mL; age 1–6 years 3546 pg/mL), CNS anomalies and metabolic/toxic disorders. There was a significant association between CSF Nf-L and serum Nf-L in cattle with neurological disorders (r2 0.2, p = 0.009). Taken together, these findings suggest the potential of Nf-L as a diagnostic tool in cattle neurology.